Transfers vs credit policy: Macroeconomic policy trade-offs during Covid-19 - Saki Bigio; Mengbo Zhang; Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2020)
The Covid-19 crisis has lead to a reduction in the demand and supply of sectors that produce goods that need social interaction to be produced or consumed. We interpret the Covid-19 shock as a shock that reduces utility stemming from 'social' goods in a two-sector economy with incomplete markets. We compare the advantages of lump-sum transfers versus a credit policy. For the same path of government debt, transfers are preferable when debt limits are tight, whereas credit policy is preferable when they are slack. A credit policy has the advantage of targeting fiscal resources toward agents that matter most for stabilizing demand. We illustrate this result with a calibrated model. We discuss various shortcomings and possible extensions to the model.
Keywords: E31; E41; E52; 330; Transfers; Credit Policy; Covid-19